Spatiotemporal Synchronization Behaviour of Logistic Map under Nearest Wave Difference using Complex Network - Maity, Debjani; Khan, Mohammad Ali (Journal of Applied Nonlinear Dynamics, 2026)
In this study, we examine the spatiotemporal synchronization behaviour of chaotic systems within the framework of a complex network. The network is characterized by dynamic coupling connections that change stochastically over time. Specifically, we consider a one-dimensional ring of coupled chaotic logistic maps, whose evolution is governed by the nearest-neighbour wave equation. Our investigation focuses on the effects of three key parameters: the degree of randomness (p), the coupling strength (ε), and the system parameter (r). Through both analytical and numerical approaches, we conduct a linear stability analysis of the synchronized steady states. Our analytical results are found to be in excellent agreement with the numerical simulations, providing a comprehensive understanding of the synchronization dynamics in this complex system.